Exploring an intensive meditation intervention for incarcerated youth. Issue 1 (11th February 2013) - Barnert, Elizabeth S.; Himelstein, Samuel; Herbert, Sarah; Garcia‐Romeu, Albert; Chamberlain, Lisa J.
<x xml:space="preserve">Abstract</x> Background We examined the experiences of incarcerated adolescent males (N = 29) who participated in a one‐day meditation retreat and 10‐week meditation programme. Method Self‐report surveys assessing mindfulness, self‐regulation, impulsivity and stress; behavioural assessments; and focus group data were examined. Results We observed significantly higher scores in self‐regulation (p = .012) and psychometric markers demonstrated psychological enhancement. No behavioural change was observed. Six themes emerged: enhanced well‐being, increased self‐discipline, increased social cohesiveness, expanded self‐awareness, resistance to meditation and future meditation practice. Conclusions Early evidence suggests that meditation training for incarcerated youth is a feasible and promising intervention.